2001
DOI: 10.1074/jbc.m008782200
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl-CoA Synthetase 2, a Mitochondrial Matrix Enzyme Involved in the Oxidation of Acetate

Abstract: Using peptide sequences derived from bovine cardiac acetyl-CoA synthetase (AceCS), we isolated and characterized cDNAs for a bovine and murine cardiac enzyme designated AceCS2. We also isolated a murine cDNA encoding a hepatic type enzyme, designated AceCS1, identical to one reported recently (Luong, A., Hannah, V. C., Brown, M. S., and Goldstein, J. L. (2000) J. Biol. Chem. 275, 26458 -26466). Murine AceCS1 and AceCS2 were purified to homogeneity and characterized. Among C2-C5 short and medium chain fatty aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
245
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(257 citation statements)
references
References 25 publications
11
245
0
1
Order By: Relevance
“…We showed that it is possible to estimate myocardial V TCA in vivo through the time-resolved 13 C MRS measurement of [5][6][7][8][9][10][11][12][13] C]citrate following the injection of hyperpolarized [1-13 C]acetate. V TCA and the dynamics of 13 C citrate labeling were independent on the amount of injected substrate and did not correlate with the dynamics of 13 C acetylcarnitine labeling.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We showed that it is possible to estimate myocardial V TCA in vivo through the time-resolved 13 C MRS measurement of [5][6][7][8][9][10][11][12][13] C]citrate following the injection of hyperpolarized [1-13 C]acetate. V TCA and the dynamics of 13 C citrate labeling were independent on the amount of injected substrate and did not correlate with the dynamics of 13 C acetylcarnitine labeling.…”
Section: Resultsmentioning
confidence: 99%
“…The signal decay of precursor and metabolites results from a combination of the effects of longitudinal relaxation (characterized by the time constant T 1 ), RF excitation, and biochemical conversion and all time courses were corrected for the effect of repeated RF excitations. The T 1 of [1-13 C]acetylcarnitine was set to 14.9 s, as previously determined in vivo [35], and that of [5][6][7][8][9][10][11][12][13] C]citrate to 20 s [46]. The acetate signal decay was treated as free parameter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It produces acetyl-CoA, which is active only in fatty acid synthesis, is highly expressed in the liver and is regulated by the same factors and patterns as FAS [14]. The other (AceCS2) is an enzyme bound to the mitochondrial matrix, found abundantly in hearts and kidneys, and synthesising acetyl-CoA active in the TCA cycle and producing [ 14 C]CO 2 from [ 14 C]acetate [15].…”
Section: Acetate Metabolic Routsmentioning
confidence: 99%